Concentrations of halogenated flame retardants and polychlorinated biphenyls in house dust from Lagos, Nigeria. Issue 11 (4th October 2021) - Akinrinade, Olumide Emmanuel; Stubbings, William A.; Abou-Elwafa Abdallah, Mohamed; Ayejuyo, Olusegun; Alani, Rose; Harrad, Stuart
Abstract : Levels of PCBs and some PBDEs in Lagos house dust have declined, demonstrating the efficacy of restrictions on these chemicals. In contrast, deca-BDE levels show no clear decline; implying its more recent restriction has yet to be fully effective. Abstract : Polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs), and hexabromocyclododecane (HBCDD) are regulated under the Stockholm Convention of the United Nations' Environment Programme; with similar concerns emerging about alternative halogenated flame retardants (alt-HFRs), the use of which is increasing as replacements for PBDEs and HBCDD. While the presence in indoor dust of PCBs, PBDEs, and HBCDDs has been reported previously in a few African locations including Lagos, Nigeria, we are unaware of similar data for alt-HFRs. The present study thus aimed to provide the first information on alt-HFRs in indoor dust in sub-Saharan Africa, and to evaluate the impact of restrictions on the use of PBDEs, HBCDD, and PCBs on their concentrations in house dust in Lagos, Nigeria. Concentrations of ∑8 PBDEs, ∑HBCDDs, ∑7 alt-HFRs, and ∑8 PCBs in 15 samples of dust from homes in Lagos, Nigeria were found to be: 43–810 (median = 300) ng g −1, <dl – 66 (median = <dl) ng g −1, 32–2600 (median = 320) ng g −1 and 3.8–61 (median = 18) ng g −1 respectively. The dominant PBDE was BDE-209, its replacement decabromodiphenyl ethane (DBDPE) was the predominant alt-HFR, while PCB-138 displayed the highest concentration of the 8 PCBs targeted. Likely due to their higher vapour pressures, concentrations of the non-arochlor PCB 11, as well as those of PCB 28, and PBDE 28 were below detection limits. Concentrations of PBDEs and PCBs reported are generally below those reported previously for Lagos, Nigeria; suggesting restrictions on their manufacture and use have been effective. In contrast, while concentrations of BDE-209 in this study were lower than in one previous study in Lagos, they exceeded those in another; implying that the more recent restrictions on the deca-BDE product have yet to be fully effective. The evidence presented here of concentrations of alt-HFRs in Nigerian house dust provide a valuable benchmark against which future trends in their concentrations may be evaluated.